Learning Arabic speaking skills using Virtual Reality via Mondly application in Metaverse: a library research - Md Noor, Mohamad Lukman Al Hakim; Othman, Muhammad Adham; Zubair, Muhammad Azhar; Md Ghalib, Mohd Feham; Sahrir, Muhammad Sabri (UniSHAMS Sdn Bhd, 2024)
This library research employs a thematic analysis methodology to explore the learning of Arabic speaking skills through the Virtual Reality (VR) Mondly application within the immersive Metaverse. Positioned at the intersection of language learning technology and the emerging Metaverse, this study systematically examines existing literature to extract, analyze, and synthesize key themes and insights relevant to this evolving educational paradigm. The findings reveal that VR can be a highly effective and immersive tool for enhancing language acquisition, particularly in learning Arabic speaking skills. This study serves as a roadmap for future developments in virtual reality language education, contributing to the ongoing evolution of language learning methodologies within this dynamic and immersive landscape.